Flipbook Records the Journey of Creating Gamelan Kaca by Thoni Konde and the Muria Raya Festival Community - Nadi, Chici Yuliana; Komariah, Arfiati Nurul (Fakultas Seni Rupa dan Desain, Institut Seni Indonesia Surakarta, 2025)
Muhammad Sulthoni or often called Thoni Konde, is an artist who creates glass gamelan works who lives in the city of Solo. The glass gamelan he created was made from waste glass materials found around him. Konde together with people in several cities make and play the glass gamelan on various occasions. Not only creating glass gamelan, Konde aspires to create a glass gamelan festival which will feature glass gamelan performances from the communities he supports. The Muria Raya Festival Foundation (FMR) through the FMR #4 collaborated with Konde and the Muria community together to create